Catholic christianity faith and practice in the 21st century : specification A - Watton, Victor W.; O'Donnell, Kevin (Dynamic learning, 2016)
Trust Victor Watton to maximise every student's potential with his trademark mix of well-paced, focused content coverage and confidence-boosting exam support; tailored to the 2016 Edexcel requirements and brought to you by the market-leading Religious Studies publisher.- Progressively builds students' subject knowledge through accessible explanations of religious and thematic concepts, topics and terms- Helps students learn, retain and revise the key content by following a clear and consistent structure that maps every topic against the specification- Offers a complete solution to assessment preparation with practice questions and expert guidance on how students can improve their responses- Enhances students' interest and understanding using a variety of engaging visual sources, textual extracts and activities to illustrate different practices, perspectives and teachings Edexcel GCSE RS Spec A: Faith and Practice in the 21st CenturyContent covered:- Area of study 1: Study of religion - Catholic Christianity - Area of study 2: Study of second religion -Islam and Judaism - Area of study 3: Philosophy and ethics- Covers the short course content for Catholic Christianity and Islam or Judaism